NTI-ULCEROGENIC EFFECT OF GENISTEIN AGAINST INDOMETHACIN-INDUCED GASTRIC ULCER IN RATS - ABDEL-RAHEEM, IHAB T; BAMAGOUS, GHAZI A; Omran, Gamal A (Asian Journal of Pharmaceutical and Clinical Research, 2016)
ABSTRACT Objectives: Free radicals generation, inflammation, and nitric oxide (NO) modulation are involved in indomethacin (IND)-induced gastric ulcers. Most of the drugs used for the treatment of gastric ulcer have various side effects. Genistein (GEN), the natural isoflavones isolated from soya bean has an antioxidant, anti-inflammatory, and NO modulating activity. These properties could make GEN a promising and safe, natural candidate against IND-induced peptic ulcers. Methods: Rats were divided into four groups. Control group; GEN group (10 mg/kg, p.o.); IND group (48 mg/kg, orally); and GEN+IND group (GEN administered 1 week before IND injection). 6 hrs after IND administration, all rats were sacrificed. Gastric juice acidity and gastric injury were evaluated directly. The levels of tumor necrosis factor alpha (TNF-Î±), myeloperoxidase (MPO), and NO were determined in gastric tissues. Moreover, glutathione (GSH), malondialdehyde (MDA), and superoxide dismutase (SOD) activity were determined in mucosal tissues. Results: Several mechanisms are involved in IND-induced ulcers as evidenced from the increase in TNF-Î±, MPO, and reduction in NO levels. In addition, free radicals also participate in the pathogenesis as evidenced from the increase in MDA levels and reduction in GSH levels and SOD activity. On the other hand, pre-administration of GEN markedly attenuated IND-induced ulcers without affecting gastric acidity, through a reduction of the elevated TNF-Î± and MPO levels. Moreover, GEN significantly restored the declined NO level and ameliorated the unbalanced oxidative stress parameters. Conclusion: GEN markedly protects against IND-induced ulcers as revealed from biochemical data and amelioration of IND-induced lesions. Therefore, GEN may be a promising candidate for protection against IND-induced gastropathy. Keywords: Genistein, Ulcers, Indomethacin, Nitric oxide, Myeloperoxidase, Tumor necrosis factor alpha.